PENINGKATAN PENGETAHUAN LANSIA DIABETES MELITUS TENTANG MENU HARIAN DAN PRINSIP 3J MELALUI MEDIA DIABETV CARE BOX SEBAGAI UPAYA PENGENDALIAN GLIKEMIK - Iis Sulastri (PITIMAS: Journal of Community Engagement in Health, 2026)
Diabetes Mellitus (DM) is a degenerative disease that requires continuous nutritional managementthrough the 3J diet principles (Schedule, Amount, and Type). This community service aims to increase the knowledge of elderly patients with DM in the Pringsewu Community Health Center work area through innovative educational media intervention. The participants were 29 elderly women aged 41-60 years. The method involved providing interactive education using the "DiabeTV Care Box" and leaflets, with evaluation conducted via pre-test and post-test. Data were analyzed using the Wilcoxon Signed Rank Test. The results of this community service showed a significant increase in knowledge (p=0.000), where the proportion of respondents in the "very good" knowledge category rose from 72.41% to 96.55%. The use of the visual media "DiabeTV Care Box" proved effective in helping the elderly understand complex dietary concepts by making them more concrete. In conclusion, nutrition education based on innovative media significantly improves the elderly's understanding of independent diabetes diet management